Comparison of the Efficacy of Caffeine with Aminophylline for Management of Infants having Apnea of Prematurity (Indus Journal of Bioscience Research, 2025)
Objective: To compare the efficacy of caffeine with aminophylline for management of infants having apnea of prematurity. Study design: Randomized Controlled Trials. Settings: Department of Pediatrics, Allied Hospital, Faisalabad. Study duration: April 2024 to September 2024. Materials & Methods: A total of 140 patients (70 in each group), both male and female infants with birth weights greater than 500 g and gestational ages between 23 and 35 weeks who had multiple episodes of preterm apnea over the course of a 24-hour period were included. Neuromuscular abnormalities, prenatal asphyxia, cerebral hemorrhage, metabolic disorders, anemia, disseminated infections, congenital illnesses, and neonates whose mothers took painkillers were not included. Using a computer-generated random number table, the patients were split into two equal groups at random. A group of seventy patients had 30 mg/kg of caffeine mixed with 5% dextrose. They also got an intravenous maintenance dose of 10 mg/kg every 24 hours.  Within three days of beginning treatment, bradycardia, hypoxia, and breathing were recorded, and the treatment's effectiveness was evaluated. Results: The average age of patients in group A was 10.69 ± 5.01 hours, whereas the average age of patients in group B was 11.84 ± 4.91 hours. There were 73 (52.14%) females and 67 (47.86%) males. The mean gestational age in groups A and B was 32.92 ± 1.55 weeks and 31.84 ± 1.42 weeks, respectively. The average blood sugar level was 82.34 ± 9.42 mg/dl.  Weight at birth was 1234.54 ± 234.72 grams on average. At one minute and five minutes, the mean Apgar score was 7.72 ± 1.43 and 8.13 ± 0.89, respectively. 45 patients (64.29%) in group B (aminophylline) and 62 patients (85.71%) in group A (caffeine) showed efficacy. The statistically significant p-value is 0.003. Conclusion: According to the study's findings, caffeine is a safer and more effective treatment for preterm apnea than aminophylline.